1995
DOI: 10.1152/ajpregu.1995.269.3.r511
|View full text |Cite
|
Sign up to set email alerts
|

Galanin and the galanin antagonist M40 do not change fat intake in a fat-chow choice paradigm in rats

Abstract: The neuropeptide galanin has been proposed to play a role in the regulation of fat intake. The purpose of the present investigation was to determine if galanin and the galanin receptor antagonist M40 would have selective effects on fat intake in a fat-chow choice paradigm in rats. Rats were adapted to 22-h access to chow alone and 2-h daily access to separate sources of fat and chow in the early dark cycle. Galanin (300 pmol, 1 nmol) or M40 (2-500 pmol) was microinjected bilaterally into the paraventricular nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
3
8
0
1
Order By: Relevance
“…Baclofen reduced shortening intake under the present limited access binge-type conditions. Previous reports have shown no effect of two peptides thought to be involved in the regulation of fat intake (galanin and enterostatin) using similar protocols [76][77][78]. Taken together, these findings indicate that food intake induced by limited access is different from food intake induced by other protocols.…”
Section: Discussionsupporting
confidence: 52%
“…Baclofen reduced shortening intake under the present limited access binge-type conditions. Previous reports have shown no effect of two peptides thought to be involved in the regulation of fat intake (galanin and enterostatin) using similar protocols [76][77][78]. Taken together, these findings indicate that food intake induced by limited access is different from food intake induced by other protocols.…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with a mitogenic function, mice overexpressing GAL develop pituitary adenomas [1112]. GAL induces its functional effects via three different G-protein coupled receptors, galanin receptor 1 (GALR1), GALR2 and GALR3 [13]. Since antagonistic roles have been reported for individual galanin receptors, it is necessary to characterize the signaling cascade of each GALR.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18]23 As for NPY, time of brain sampling is a critical factor for the effect of an HF diet on galanin concentration in the PVN and median eminence. [13][14][15][16][17][18]23 As for NPY, time of brain sampling is a critical factor for the effect of an HF diet on galanin concentration in the PVN and median eminence.…”
Section: G Alanin and N Eurotensinmentioning
confidence: 99%
“…It preferentially stimulates carbohydrate intake 7,8 (see also Chapter 25 by Leibowitz in this book) and to a lesser extent fat intake. [13][14][15] Other experiments do not confirm this unique effect on fat intake 16,17 and/or suggested that individual food preferences might play a role in the feeding response to galanin injection. 9,10 Galanin, a 29-AA peptide, is synthetized in neurons of the PVN as well as in the ARC and other brain areas.…”
Section: Introductionmentioning
confidence: 99%